Sibirya'dan - Radlov, Friedrich Wilhelm, 1837-1918. ([Ankara] [Ankara] [Ankara])
<3> cilt (1. c., 1. kitap lxx, 258 sayfa, [1] yaprak portre, 4 yaprak resim ; 1. c., 2. kitap sayfa [261]-631, [11] yaprak resim, portre, çizim, [2] sayfa plan ; 2. c., 2. kitap sayfa [301]-555, [3] yaprak resim, 1 katlı harita)